Human Resources in India - Sunkad, Smt Gayatri (Research Parks Publishers, 2022)
The human resources are also considered as the resources of the nation also. Like natural resources, these are also essential assets of the any country. The human resources are considered as the equal gaining importance compared to natural resources. Like natural resources, the population is also considered to be the wealth of a country. The people living in a country constitute the population of that country, which consists of children, adults, and senior citizens. Those under 14 years are considered children, those between 15 and 60 years are considered adults, and those above 60 are identified as senior citizens. Adults are capable of working, and they form the national wealth. People with knowledge, skill, and abilities form the human resource of that country. Since the population of adults is more in India, there is an increase in the workforce. If good education, training and health facility are provided to human resources, they can be transformed into human capital. They possess the capability to increase the national income and transform society, that is population is it an asset. This paper with methodology analyses the existing situation of human resources in India and this paper theoretically analyses the status of human resources with comparing to other natural resources.